EVALUASI PERILAKU DEFORMASI VERTIKAL BENDUNGAN SERMO BERDASARKAN DATA INSTRUMENTASI GEOTEKNIK - Rizka Sartika Hutami; Hari Nugroho; Sutarto Edhisono (Racic : Rab Construction Research, 2023)
The vertical deformation of the dam is one of the important parameters to be evaluated both during the construction and post-construction periods. Abnormal deformation behavior can cause various problems that threaten the safety of the dam. Evaluation is very important to do, especially on the Sermo Dam which has been loaded for more than 25 years to knows its behavior. Identification of abnormal behavior is done by evaluating the results of the vertical deformation analysis based on the instrumentation reading data against the acceptance criteria. In the construction, the vertical strain value compared with the depth below crest value resulted in abnormal behavior. However, evaluation of the settlement that occurs results in normal behavior. In the post-construction, evaluation with Sherard (1965) and ICOLD (1993) criteria resulted in abnormal conditions at certain elevations. However, evaluation based on the settlement index and acceptance criteria of Sowers (1965) and Hunter and Fell (2003) resulted in normal conditions.